Design of Concrete Sheet Pile Revetment As A River Protector And Recreation Facilities - Arbianto, Reki; Gunarso, Gunarso; Sungkono, Kukuh Kurniawan Dwi (Science and Technology Research Centre, Universitas PGRI Semarang, 2020)
Revetment is a strengthening structure on river slopes from erosion. Erosion of river slopes can widen the wet cross section of the river and increasing scouring can endanger the surrounding buildings. The construction of the Demangan Water Gate in Surakarta City (Phase I) is planned at the mouth of the Pepe river downstream. The construction work will result in changes in river morphology, therefore it is necessary to protect the river slopes so that landslides do not occur. Apart from being a river slope protector, the Revetment design can also be a recreation area and an inspection road. The construction to be used is a concrete sheet pile revetment with reinforcement of the piles behind it as an anchor. Between the concrete sheet pile and the concrete pile, it is connected by a beam-slab structure so that it becomes a portal system. River slope stability analysis using GeoStudio2018 R2 software. River slope conditions that may occur are applied in several modeling, including: River slope conditions without Revetment reinforcement, River slope conditions with Revetment reinforcement, Conditions when changes in river water level elevation occur and river slope conditions when erosion occurs. Based on the results of modeling analysis on the original slope when the river water level increase then recedes has the smallest safe number (SF = 1,822). This is because on the back side of the Revetment, the active soil pressure is in a saturated condition, while the front side of the Revetment loses hydrostatic pressure as a counterweight. The highest safety number is in slope modeling with Revetment strengthening when the river water level increase (SF = 3.114), because the hydrostatic pressure on the back and front of the Revetment is balanced. Revetment construction on river slopes increases the safety rate by 30.64% - 43.70%. With the strengthening of the river slopes, it is hoped that it can provide sufficient security from the main function of protecting the river slopes and obtaining additional functions as a recreation area.